Peningkatan Kemampuan Membaca Anak Melalui Permainan Kalender Kata di Taman Kanak-Kanak - Efita, Ade; Yulsyofriend, Yulsyofriend (Penerbit Aksara Rentaka Siar (ARS), 2020)
The purpose of this study is to describe the improvement of children's reading skills through the media of word calendar games. This type of research is classroom action research (CAR) that uses qualitative and quantitative approaches. The subjects of this study were the teacher and B1 kindergartens Aisyiyah with a total of 14 people. The results showed an increase in the ability to read children through the word calendar game media has increased. The percentage of completeness of learning cycle I only 36%, then in cycle II an increase in children's reading ability through the media calendar play words that is equal to 86%